Analysis of Service Quality at Educational Tourism at Puncak Bogor Safari Park in Improving Visitor Satisfaction - Parantika, Asep; Noor Sultan Irgi Wibowo; Muhammad Iqbal Baskoro (The Postgraduate School of Tourism Sahid Polytechnic, 2025)
Purposes: This study aims to improve the management of Taman Safari Puncak Bogor by focusing on the quality of service that affects visitor satisfaction. This study identifies the most important components of service quality, including reliability, responsiveness, assurance, empathy, and physical evidence. By knowing these components, managers can be more effective in providing resources to meet visitor expectations. Research methods: According to this study, there are five main dimensions of service quality that affect the visitor experience of Taman Safari Puncak Bogor: reliability, responsiveness, assurance, empathy, and tangibles. Although the evaluations are positive, the main problems are the lack of interaction in educational information and speed of service. To improve the visitor experience, solutions include automated ticketing systems and interactive digital technologies. Results and discussion: The results of the study at Taman Safari Indonesia Puncak Bogor showed that workers were very committed to handling customer complaints. However, the complaint handling process still needs to be improved, especially in terms of department coordination and quick response. A SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis showed several strengths. Examples of strengths include friendly and professional staff and receiving positive reviews. Weaknesses, such as poor queue management and inadequate public facilities on holidays, have been a concern. Using queue management technology and promotions are opportunities to improve the visitor experience, while competition from other destinations and changes in consumer behavior are threats. This study aims to provide practical advice to management on how to improve service quality and attract more people. Implication: This study emphasizes that Taman Safari Indonesia Puncak Bogor needs to improve its services to better meet visitors’ expectations. Key improvements should focus on accelerating services and providing more interactive educational content. The application of technology such as automated ticketing systems and digital guide applications can streamline the service process and create a more engaging learning experience. By adopting these strategies, Taman Safari can strengthen its position as a leading educational tourism destination in Indonesia and contribute to sustainable tourism growth.